Composite treatment agent, its preparation and use in perchlorate waste water

CN121361901BActive Publication Date: 2026-10-27CENT SOUTH UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511905250.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-17
Publication Date
2026-10-27
Estimated Expiration
2045-12-17

AI Technical Summary

Technical Problem

[0008]针对高氯酸盐废水特别是含硝氮、氨氮的复杂废水难于异养微生物降解的问题,本发明第一目的在于,提供所述的复合处理剂,旨在基于成分的联合协同,改善高氯酸盐废水特别是复杂废水的异养微生物降解效率和效果

Benefits of technology

[0063]本发明提供了一种改性高岭石及其O/W非对称原位沉积制备方法。本发明研究表明,所述的改性高岭石能够适配高氯酸盐的异养微生物降解效果,有助于改善其降解效率和效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121361901B_ABST
    Figure CN121361901B_ABST
Patent Text Reader

Abstract

The application belongs to the field of wastewater treatment, and particularly relates to a composite treatment agent, preparation thereof and application in perchlorate wastewater, and the composite treatment agent is characterized in that it comprises modified kaolinite and enzymes; the modified kaolinite is a material of ferroferric oxide partially in-situ coated kaolinite, which comprises kaolinite and ferroferric oxide nanoparticles in-situ deposited on part of the surface of the kaolinite; the enzymes comprise protease and / or lipase. The application proposes a material of ferroferric oxide partially in-situ coated kaolinite, which is based on the combination of the special physicochemical characteristics of kaolinite and the special partial in-situ coating characteristics of the ferroferric oxide, so as to adapt to the degradation characteristics of perchlorate heterotrophic microorganisms, and help to improve the degradation effect of perchlorate, especially for complex perchlorate wastewater containing ammonia nitrogen and nitrate nitrogen simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to the preparation and application of a treatment agent that improves the degradation effect of perchlorate by heterotrophic microorganisms. Background Technology

[0002] Perchlorate is used extensively in fireworks manufacturing and aerospace. The main hazards of perchlorate are that it enters the body through the digestive and respiratory systems (such as drinking water contaminated with perchlorate and breathing air containing perchlorate dust), and it has certain toxic effects on the thyroid, nervous system, growth and development, and reproductive system of organisms.

[0003] Methods for removing perchlorate from wastewater include activated carbon adsorption, chemical reduction, and biological methods. For example, patent document CN119161063A1 discloses a method for treating perchlorate wastewater, specifically describing a method for biodegrading perchlorate wastewater in a microbial catalytic tank. Patent document CN118324244A discloses a method for efficiently degrading perchlorate based on biorenewable resin and its application.

[0004] Among these methods, biological methods have advantages such as ease of operation and low operating costs. Biological methods include autotrophic reduction and heterotrophic reduction (also called heterotrophic microbial degradation of perchlorate).

[0005] Currently, heterotrophic microbial degradation of perchlorate is widely considered a promising technology for perchlorate removal, and it is more suitable for large-scale industrial wastewater treatment. This method typically requires an external organic carbon source as an electron donor and has advantages such as rapid degradation rate and ease of operation and management.

[0006] However, the heterotrophic microbial degradation of perchlorate currently faces the following main problems: ① Perchlorate degradation is poor at low temperatures (2~5℃) because most reducing bacteria are mesophilic and cannot survive below 5℃; ② High concentrations of nitrate and perchlorate coexist in the wastewater system, and nitrate (referred to as nitrate nitrogen) will be preferentially degraded, resulting in a significant decrease in the rate of perchlorate microbial degradation; ③ The coexistence of ammonia nitrogen and perchlorate in the wastewater system will also significantly reduce the rate of perchlorate microbial degradation.

[0007] In summary, the removal of perchlorate wastewater containing both ammonia nitrogen and high concentrations of nitrate nitrogen, or perchlorate at low temperatures, is challenging, particularly the simultaneous removal of perchlorate, nitrate nitrogen, and ammonia nitrogen. To address this key issue, a highly efficient treatment method for the heterotrophic microbial degradation of perchlorate is urgently needed. Summary of the Invention

[0008] To address the problem that perchlorate wastewater, especially complex wastewater containing nitrate nitrogen and ammonia nitrogen, is difficult to degrade by heterotrophic microorganisms, the primary objective of this invention is to provide the aforementioned composite treatment agent, which aims to improve the efficiency and effectiveness of heterotrophic microbial degradation of perchlorate wastewater, especially complex wastewater, based on the combined synergistic effect of its components.

[0009] The second objective of this invention is to provide a method for preparing the aforementioned composite treatment agent and its application in wastewater treatment.

[0010] The heterotrophic microbial degradation effect on perchlorate wastewater is not ideal, especially for complex perchlorate wastewater containing ammonia nitrogen and nitrate nitrogen, where the degradation activity and efficiency are significantly increased. To address the treatment challenges of this complex wastewater, this invention, after in-depth research, provides the following improved solution:

[0011] Composite treatment agents, including modified kaolinite and enzymes;

[0012] Modified kaolinite is a kaolinite material partially coated with iron oxide in situ, which includes kaolinite and iron oxide nanoparticles deposited in situ on part of the surface of kaolinite.

[0013] The enzymes mentioned include proteases and / or lipases.

[0014] This invention proposes a partially in-situ coated kaolinite material with iron(III) oxide. Based on the unique physicochemical properties of kaolinite and the specific characteristics of partially in-situ coating of iron(III) oxide, this material is well-suited to the heterotrophic microbial degradation of perchlorate, thus improving the degradation effect, particularly for complex perchloric acid wastewater containing both ammonia and nitrate nitrogen. Furthermore, the innovative combination of this partially in-situ coated kaolinite material with proteases and lipases further enhances synergy, strengthening the heterotrophic microbial degradation activity and efficiency of perchlorate wastewater, especially complex perchlorate wastewater.

[0015] In the modified kaolinite of this invention, the area covered by iron oxide nanoparticles accounts for 30-60% of the kaolinite surface area.

[0016] Preferably, iron oxide is deposited on one surface of kaolinite.

[0017] Preferably, the weight ratio of ferric oxide to kaolinite is 0.2~0.4:1.

[0018] In this invention, the method for preparing modified kaolinite involves mixing kaolinite and a coupling agent, then adding water and a hydrophobic solvent for ultrasonic emulsification to obtain an O / W type emulsion.

[0019] Subsequently, water-soluble ferric salts, water-soluble ferrous salts, and alkaline components were added to the O / W emulsion, and iron oxide nanoparticles were deposited in situ on the surface of kaolinite in contact with the aqueous phase in the O / W emulsion to obtain the modified kaolinite.

[0020] This invention also provides an in-situ precipitation method for O / W type iron oxide, which innovatively disperses kaolinite at the water-oil interface of an O / W type emulsion, immersing the kaolinite in both the oil and aqueous phases. Subsequently, iron oxide nanoparticles are selectively precipitated in situ on the surface of the kaolinite on the aqueous side. The method described in this invention can prepare partially asymmetric modified kaolinite structural materials, and the materials prepared by this method are adaptable to the conditions of perchlorate heterotrophic microbial degradation, achieving superior perchlorate degradation effects. In particular, it can also achieve excellent degradation rates and efficiencies for complex perchlorate wastewater containing ammonia nitrogen and nitrate nitrogen, which is difficult to treat effectively with existing technologies.

[0021] In this invention, the coupling agent is at least one of conventional titanate coupling agents and silane coupling agents.

[0022] For example, the silane coupling agent can be a conventional coupling agent containing a (RO)3Si- structure. The titanate coupling agent can be a conventional coupling agent containing a (RO)3Ti- structure. R is methyl, ethyl, propyl, or butyl, etc.

[0023] The silane coupling agent may be at least one of KH-570, KH-560, KH-590, vinyltriethoxysilane, etc. The titanate coupling agent may be at least one of isopropyl tris(dioctyl pyrophosphate) titanate, KR-38S (isopropyl di(dioctyl pyrophosphate) titanate), TTS (tetraisopropyl bis(dioctyl pyrophosphate) titanate), etc.

[0024] In this invention, kaolinite inherently possesses an asymmetric structure, with its crystals formed by the stacking of "silicon-oxygen tetrahedral sheets (Si-O)" and "aluminum-oxygen octahedral sheets (Al-OH)" through hydrogen bonds, and the surface properties of the two layers are completely different. By treating kaolinite with the aforementioned coupling agent, the resulting modified kaolinite can be transformed into an "amphiphilic structure" with "one side (aluminum-oxygen side) being strongly hydrophobic and the other side (silicon-oxygen side) being hydrophobic / weakly hydrophilic," thereby facilitating the in-situ deposition of iron(III) oxide on the weakly hydrophilic side under thermodynamic driving.

[0025] The weight ratio of kaolinite to coupling agent is 1:0.005~0.025; preferably 1:0.01~0.015; and further preferably 1:0.01~0.05.

[0026] In this invention, kaolinite and a coupling agent are combined, and then ultrasonically emulsified with water and a hydrophobic solvent to obtain an O / W type emulsion, in which the surface of kaolinite is partially immersed (in contact) in the oil phase and partially immersed (in contact) in the aqueous phase. Subsequently, water-soluble ferric salt, water-soluble ferrous salt and alkaline components are added to the O / W type emulsion, and iron oxide nanoparticles are deposited in situ on the surface of the kaolinite immersed in the aqueous phase to obtain the modified kaolinite.

[0027] The hydrophobic solvent is C4~C 10 Hydrocarbon solvents; for example, cyclopentane, cyclohexane, cycloheptane, n-hexane, n-heptane, etc.

[0028] Preferably, the volume ratio of water to hydrophobic solvent is 1:0.5~5; more preferably 1:1~1.5.

[0029] The volume-to-weight ratio of water and hydrophobic solvent to kaolinite is 5-20 mL / g, and more specifically 10-15 mL / g.

[0030] The water-soluble ferrous salt is at least one of ferrous chloride, ferrous sulfate, ferrous nitrate, and ferrous acetate.

[0031] Preferably, the water-soluble iron salt is at least one of ferric chloride, ferric sulfate, and ferric nitrate;

[0032] In this invention, Fe 2+ Fe 3+ The molar ratio is 2~4:1;

[0033] The mass ratio of kaolinite to water-soluble ferrous salt is 2-5:1, and more preferably 3-4:1. This invention has found that at this preferred ratio, the simultaneous removal efficiency of nitrate nitrogen, ammonia nitrogen, and perchlorate from wastewater can be further improved.

[0034] In this invention, there are no special requirements for the temperature of in-situ deposition; for example, it can be 50~60℃.

[0035] Preferably, the alkaline component is at least one of NH3·H2O, NaOH, and KOH, and its solute concentration can be 1~3 mol / L.

[0036] Preferably, the pH of the in-situ deposition process is 10-12.

[0037] The in-situ deposition reaction time is 2-3 hours.

[0038] In this invention, the in-situ deposition process can be carried out in protective gases such as Ar and nitrogen.

[0039] This invention demonstrates that by innovatively combining modified kaolinite with protease and lipase, the asymmetric iron oxide composition and asymmetric structure of kaolinite surface can be utilized to enhance the synergistic activity of protease and lipase, thereby improving the heterotrophic microbial degradation activity and efficiency of complex perchlorate wastewater.

[0040] This invention innovatively discovers that, using the modified kaolinite, its iron oxide nano-coating layer easily binds to proteases, while the uncoated kaolinite easily binds to lipases. The combination of the modified kaolinite and enzymes in this invention can play a synergistic role. For wastewater containing ammonia nitrogen and high concentrations of nitrate nitrogen and perchlorate, it can significantly improve the heterotrophic microbial degradation effect of perchlorate and achieve simultaneous removal of nitrate nitrogen, ammonia nitrogen and perchlorate. At the same time, it can significantly improve the heterotrophic microbial degradation effect of perchlorate at low temperatures (2℃~6℃, especially 3~5℃).

[0041] In this invention, both the lipase and protease are activated enzymes. The activation method can be any method recognized in the industry; in this invention, it is preferred to activate the enzymes in a phosphate buffer solution.

[0042] Preferably, in the composite treatment agent, the enzymes include protease and lipase.

[0043] Preferably, the content of the protease in the composite treatment agent can be 5000~20000U / g, more preferably 8000~16000U / g; even more preferably 9000U / g~11000U / g; and the content of the lipase can be 3000~20000U / g, more preferably 4000~16000U / g; even more preferably 5000~7000U / g.

[0044] The present invention also provides a method for preparing the composite treatment agent, wherein the components are combined to obtain the composite agent.

[0045] For example, its preparation method is as follows:

[0046] Step 1 (S1): Activate lipase and protease separately to obtain activated lipase and protease.

[0047] Step 2 (S2): Partially coating kaolinite with iron oxide nanoparticles to obtain modified kaolinite.

[0048] Step 3 (S3): Mix the activated lipase, protease and modified kaolinite in a certain proportion to obtain a series of treatment agents.

[0049] The present invention also provides an application of the aforementioned composite treatment agent for the treatment of perchlorate wastewater.

[0050] In the application described in this invention, the concentration of perchlorate in the perchlorate wastewater is 50~1500 mg / L, further 200~1200 mg / L; and even further 700~1200 mg / L. In this invention, even for high-concentration wastewater, it can still obtain excellent degradation ability, especially under low temperature and complex water conditions.

[0051] Preferably, the perchlorate wastewater contains ammonia nitrogen and / or nitrate nitrogen simultaneously;

[0052] Furthermore, thanks to the excellent performance of the composite treatment agent described in this invention, it can be adapted to wastewater systems containing nitrate nitrogen, ammonia nitrogen, and perchlorate that are difficult to treat in the industry.

[0053] For example, as an optional scheme, the perchlorate concentration (calculated as perchlorate ion) in the perchlorate wastewater is 50~1500 mg / L, and can be further 200~1200 mg / L; for example, it can be wastewater with a concentration of 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 700 mg / L, 800 mg / L, 900 mg / L, 1000 mg / L, 1100 mg / L, 1200 mg / L, and any combination thereof. The nitrate concentration (calculated as nitrate nitrogen) is 50~800 mg / L, for example 100~700 mg / L; further, it can be wastewater with a concentration of 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 700 mg / L, and any combination thereof. The ammonia nitrogen concentration is 20~200 mg / L, for example, it can be 80~120 mg / L; for example, it can be wastewater with a further range of 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 130 mg / L, 1400 mg / L and any combination thereof.

[0054] In this invention, apart from the addition of the aforementioned treatment agent, the other operations and parameters of the perchlorate heterotrophic microbial degradation process can be conventional.

[0055] Preferably, the amount of the composite treatment agent used in the treatment process is 100~500mg / L, for example, it can be 200~400mg / L, and more preferably 250~350mg / L.

[0056] For example, during the degradation of perchlorate by heterotrophic microorganisms, the pH value is controlled between 7 and 7.5, the temperature is between 2 and 35°C, and the dissolved oxygen is between 0.05 and 0.2 mg / L.

[0057] For example, in the wastewater treatment process of the present invention, activated sludge is added to the sequencing batch reactor in advance, followed by the treatment agent of the present invention and the wastewater to be treated, and then heterotrophic microbial degradation treatment is carried out.

[0058] Preferably, the activated sludge is anaerobic sludge from a wastewater treatment plant, with a sludge concentration (MLSS) of 3000~5000 mg / L.

[0059] In this invention, there are no special requirements for the temperature of the wastewater treatment process. However, thanks to the innovative use of the treatment method, this invention can achieve high-temperature treatment at low temperatures that are difficult to achieve in the industry. The low temperature is, for example, 2~10°C, and can be further 3~5°C.

[0060] The wastewater treatment time of this invention can be reasonably adjusted as needed, for example, it can be 4 days to 7 days.

[0061] In this invention, the aforementioned treatment agent can be added to conventional heterotrophic microbial degradation technology for perchlorate, effectively enriching bacterial strains capable of degrading perchlorate and thus improving the degradation efficiency of perchlorate by heterotrophic microorganisms. Furthermore, the addition of this treatment agent solves the major problems of poor perchlorate degradation efficiency and difficulty in achieving simultaneous removal of nitrate, ammonia, and perchlorate by heterotrophic microorganisms when temperatures are below 5°C (3-5°C) and ammonia nitrogen and high concentrations of nitrate nitrogen coexist with perchlorate.

[0062] Beneficial effects:

[0063] This invention provides a modified kaolinite and its O / W asymmetric in-situ deposition preparation method. Research in this invention shows that the modified kaolinite is adaptable to the heterotrophic microbial degradation of perchlorate, thus helping to improve its degradation efficiency and effectiveness.

[0064] The present invention also provides a combination of the modified kaolinite, lipase, and protease, which can significantly improve the heterotrophic microbial degradation efficiency and effect of perchlorate wastewater based on the modified kaolinite partially supported by iron oxide and the special compatibility between lipase and protease. In particular, it can achieve excellent degradation efficiency and low-temperature degradation ability for complex perchlorate wastewater containing nitrate nitrogen and ammonia nitrogen that is difficult to treat in the industry. Attached Figure Description

[0065] Figure 1 SEM images of untreated kaolinite (left) and modified kaolinite prepared in Example 1 (right). As can be seen from the images, iron oxide nanoparticles are deposited on the surface of the kaolinite.

[0066] Figure 2The image shows the UV-Vis spectrum of the modified kaolinite enzyme activity test. A strong absorption peak is observed near 652 nm, indicating good enzyme activity.

[0067] Figure 3 The XRD patterns of modified kaolinite prepared at different pH values ​​are shown. As can be seen from the figures, the diffraction peaks of Fe3O4 are located at 30.21°, 35.48°, 43.29°, 53.74°, and 57.09°, corresponding to crystal planes (220), (311), (400), (422), and (511), respectively, consistent with the standard PDF card (JCPDS Card NO. 89—4319) for Fe3O4. The diffraction peak of kaolinite is located at 62.5°, corresponding to crystal plane (240), consistent with the standard PDF card JCPDS No. 01-078-2109.

[0068] Figure 4 The figures show the room temperature hysteresis curves of the modified kaolinite prepared at different pH values. As can be seen from the figures, none of the prepared modified kaolinite exhibited hysteresis, and all produced closed hysteresis curves while maintaining a high saturation magnetization, further proving that the iron oxide nanoparticles are coated on the surface of the kaolinite.

[0069] Figure 5 This is a graph showing the colony test results, with attached... Figure 5 -a: Microbial community in sludge from wastewater containing only 800 mg / L perchlorate at 26℃, without the addition of any treatment agents. (Attached) Figure 5 -b: Microbial community in sludge from wastewater containing 600 mg / L nitrate nitrogen, 100 mg / L ammonia nitrogen, and 800 mg / L perchlorate at 3℃, without the addition of any treatment agents. (See attached image) Figure 5 -c: Microbial community in sludge after adding 300 mg / L of treatment agent to wastewater containing 600 mg / L nitrate nitrogen, 100 mg / L ammonia nitrogen, and 800 mg / L perchlorate at 3℃. (From Appendix) Figure 5 -a~attachment Figure 5 -c indicates that, compared to not adding any treatment agent (see attached image) Figure 5 -a and appendix Figure 5 -b) Compared to adding treatment agents (with) Figure 5 -c) The percentages of β-proteobacteria and β-Acidobacteriota, which are beneficial for the heterotrophic degradation of perchlorate, were significantly increased. For wastewater containing only perchlorate (within the appendix) without the addition of treatment agents... Figure 5 Compared to -a), wastewater systems with low temperature and simultaneous presence of nitrate nitrogen, ammonia nitrogen, and perchlorate (see appendix) Figure 5-b) The percentages of β-proteobacteria and β-Acidobacteriota, which are beneficial to the degradation of perchlorate by heterotrophic microorganisms, both decreased. Detailed Implementation

[0070] To make the objectives, methods, and advantages of this invention clearer, the technical solutions adopted in this application are described in detail below with reference to examples. The specific embodiments described herein are for illustrative purposes only and are not intended to construe as...

[0071] This invention is intended to limit the scope of the invention.

[0072] Experimental materials:

[0073] The perchlorate wastewater was prepared for experimental simulation, with perchlorate concentration of 50-1500 mg / L, nitrate nitrogen concentration of 50-800 mg / L, and ammonia nitrogen concentration of 20-200 mg / L.

[0074] Some testing methods and standards:

[0075] ClO4 - The determination of nitrogen was performed using a CIC-D120 ion chromatograph; the determination of nitrate nitrogen was performed according to the ultraviolet spectrophotometric method of HJ / T 346-2007; and the determination of ammonia nitrogen was performed according to HJ 535-2009.

[0076] The perchlorate heterotrophic microbial degradation treatment process of the present invention includes the following steps:

[0077] (1) Inoculation sludge. The sludge used for heterotrophic microbial degradation of perchlorate in this invention is derived from anaerobic sludge from a conventional sewage treatment plant (for example, anaerobic sludge from a sewage treatment plant in Yuelu District, Changsha City), and the sludge concentration can be, for example, 3000~5000 mg / L;

[0078] (2) During the degradation of perchlorate by heterotrophic microorganisms, the concentration of perchlorate in the influent is 50~1500mg / L, sodium acetate is added to the influent as a carbon source, the pH value is 7.0~7.5, the pH value is controlled by the pH automatic control system, the temperature is between 2~35℃, the dissolved oxygen is 0.05~0.2mg / L, and the anaerobic stirring lasts for 6~18 hours.

[0079] (3) The reactor for the degradation of perchlorate by heterotrophic microorganisms is a sequencing batch reactor with an effective volume of 5L. A stir bar is placed at the bottom, and the internal device is equipped with an online pH and dissolved oxygen monitoring probe. The online monitoring probe transmits the data to the PLC control cabinet in real time. The PLC control cabinet controls the peristaltic pump to stop and start by setting the pH value, and adds acid solution. The added acid solution is a 3mol / L H2SO4 solution.

[0080] In this invention, the enzyme can be activated using conventional methods, for example:

[0081] Add 2g of lipase to a 100mL stoppered conical flask, add 50mL of phosphate buffer solution (0.05mol / L, pH 7.5), place in a constant temperature shaker, shake to evenly disperse the enzyme in the buffer solution, control the temperature at 25~30℃, and activate the enzyme for 30min.

[0082] Add 2g of protease to a 100mL stoppered conical flask, add 50mL of phosphate buffer solution (0.05mol / L, pH 7.5), place in a constant temperature shaker, shake to evenly disperse the enzyme in the buffer solution, control the temperature at 25~30℃, and activate the enzyme for 30min.

[0083] Example 1

[0084] Step 1: Preparation of modified kaolinite:

[0085] Raw kaolinite was soaked in distilled water, washed, dried, and then crushed using a pulverizer, passing through a 200-mesh sieve. A silane coupling agent (such as KH-570) was added to the kaolinite powder (7g of kaolinite) passing through the 200-mesh sieve (the weight ratio of kaolinite to silane coupling agent was 1:0.01). The mixture was stirred at 60°C for 1 hour, then poured into a 250mL three-necked flask. 50mL of deionized water and 50mL of n-hexane were added to the flask, and the mixture was stirred at room temperature for 10 minutes, followed by ultrasonic emulsification for 20 minutes to obtain an O / W type Pickering emulsion (at this point, the kaolinite particles were adsorbed onto the surface of the n-hexane oil droplets, with half of the particles in the oil phase and half in the aqueous phase). The prepared O / W type Pickering emulsion was protected with high-purity nitrogen for 10 min. A mixed solution of ferrous chloride and ferric chloride in a certain proportion was then slowly added dropwise to the emulsion at room temperature. The mixture was stirred for 30 min to ensure uniform dispersion. The temperature was then raised to 40℃, and NaOH solution was slowly added at this temperature to adjust the pH of the emulsion to 11. The reaction was stopped when a black precipitate appeared. After the reaction was complete, 50 mL of anhydrous ethanol was added to a three-necked flask to break the emulsion. The mixture was centrifuged at 3000 rpm for 10 min, and the black precipitate was collected. The black precipitate was washed 3-5 times alternately with deionized water and ethanol to remove residual oil phase, unreacted salts, and coupling agents. The washed black precipitate was vacuum dried at 60℃ for 12 hours and then ground to obtain kaolinite particles coated with magnetite nanoparticles, abbreviated as modified kaolinite (Fe3O4:kaolinite = 0.3:1).

[0086] The Fe in the ferrous chloride and ferric chloride mixed solution 2+ Fe3+ The molar ratio of kaolinite to ferrous chloride is 3:1, the mass ratio of kaolinite to ferrous chloride is 3:1, the molar concentration of NaOH solution is 3M, and the total reaction time from the addition of silane coupling agent to kaolinite powder to the appearance of black precipitate is 3h.

[0087] Step 2: Composite treatment agent

[0088] Prepare a phosphate buffer solution (pH 7.5, 0.05 mol / L) and preheat it in a water bath at 25–30 °C. Weigh out lipase (6000 U / g carrier) and protease (10000 U / g carrier) according to the specified ratio, add them to the buffer solution, and stir at 28 °C and 200 rpm for 15–20 min to obtain a homogeneous enzyme solution. Add modified kaolinite to the enzyme solution, adjust the temperature to 32 °C, and maintain gentle stirring at 200–300 rpm for 2–3 h. After binding is complete, separate the carrier-enzyme complex using a magnet (magnetic response time <30 s), wash 2–3 times with buffer solution (to remove unbound free enzyme), and it is ready for subsequent catalytic reactions. The obtained complex is the treatment agent added to the perchlorate heterotrophic microbial degradation process of this invention (hereinafter referred to as: treatment agent).

[0089] Example 2

[0090] Compared with Example 1, the only difference is that the conditions of step 1 are changed, and only the weight ratio of kaolinite and silane coupling agent in step 1 is changed to 1:0.02. All other operations and parameters are the same as in Example 1.

[0091] Example 3

[0092] Compared with Example 1, the only difference is that the conditions of step 2 are changed, the enzyme contains only protease, and the protease loading is 16000 U / g carrier. All other operations and parameters are the same as in Example 1.

[0093] Example 4

[0094] Compared with Example 1, the only difference is that the conditions of step 2 are changed, the enzyme contains only lipase, and the lipase loading is 16000 U / g carrier. All other operations and parameters are the same as in Example 1.

[0095] Example 5

[0096] Compared with Example 1, the only difference is that the conditions of step 2 are changed, and the immobilization amount of protease and lipase is changed. Specifically, the immobilization amount of lipase is 10,000 U / g carrier, and the immobilization amount of protease is 15,000 U / g carrier. All other operations and parameters are the same as in Example 1.

[0097] Example 6

[0098] Compared with Example 1, the only difference is that the step conditions are changed. The difference is as follows:

[0099] Step 1:

[0100] Raw kaolinite was soaked in distilled water, washed, dried, and then crushed using a pulverizer, passing through a 200-mesh sieve. A silane coupling agent (such as vinyltriethoxysilane) was added to the kaolinite powder (8g of kaolinite) passing through the 200-mesh sieve (the weight ratio of kaolinite to silane coupling agent was 1:0.015). The mixture was stirred at 60°C for 1 hour, then poured into a 250mL three-necked flask. 50mL of deionized water and 70mL of n-hexane were added to the flask, and the mixture was stirred at room temperature for 10 minutes, followed by ultrasonic emulsification for 20 minutes to obtain an O / W type Pickering emulsion (at this point, the kaolinite particles were adsorbed onto the surface of the n-hexane oil droplets, with half of the particles in the oil phase and half in the aqueous phase). The prepared O / W type Pickering emulsion was protected with high-purity nitrogen for 10 minutes. Then, a certain proportion of a mixed solution of ferrous chloride and ferric chloride was slowly added dropwise to the emulsion at room temperature. The mixture was stirred for 30 minutes to ensure uniform dispersion. The temperature was then raised to 40°C, and NaOH solution was slowly added at this temperature to adjust the pH of the emulsion to 12. The reaction was stopped when a black precipitate appeared. After the reaction was complete, 50 mL of anhydrous ethanol was added to a three-necked flask to break the emulsion. The mixture was centrifuged at 3000 rpm for 10 minutes, and the black precipitate was collected. The black precipitate was washed 3-5 times alternately with deionized water and ethanol to remove residual oil phase, unreacted salts, and coupling agents. The washed black precipitate was vacuum dried at 60°C for 12 hours, and then ground to obtain kaolinite particles coated with magnetite nanoparticles, abbreviated as modified kaolinite. The Fe in the ferrous chloride and ferric chloride mixed solution... 2+ Fe 3+ The molar ratio of kaolinite to ferrous chloride is 2:1, the mass ratio of kaolinite to ferrous chloride is 4:1, the molar concentration of NaOH solution is 3M, and the total reaction time from the addition of silane coupling agent to kaolinite powder to the appearance of black precipitate is 3h.

[0101] Step 2: Composite treatment agent

[0102] Prepare a phosphate buffer solution (pH 7.5, 0.05 mol / L) and preheat it in a water bath at 25–30 °C. Weigh out lipase (5500 U / g carrier) and protease (11000 U / g carrier) according to the specified ratio, add them to the buffer solution, and stir at 28 °C and 200 rpm for 15–20 min to obtain a homogeneous enzyme solution. Add modified kaolinite to the enzyme solution, adjust the temperature to 32 °C, and maintain gentle stirring at 200–300 rpm for 2–3 h. After binding is complete, separate the carrier-enzyme complex using a magnet (magnetic response time < 30 s), wash 2–3 times with buffer solution (to remove unbound free enzyme), and it is ready for subsequent catalytic reactions. The obtained complex is the treatment agent added to the perchlorate heterotrophic microbial degradation process of this invention (hereinafter referred to as: treatment agent).

[0103] Comparative Example 1

[0104] Compared with Example 1, the only difference is that in step 1, the kaolinite was not treated; instead, it was directly processed in step 2. All other operations and parameters were the same as in Example 1, resulting in comparative treatment agent 1.

[0105] Comparative Example 2

[0106] Compared with Example 1, the only difference is that in step 1, the modified kaolinite material was not prepared using the emulsion method, that is, no coupling agent was added. In addition, an equal volume of water was used to replace n-hexane. All other operations and parameters were the same as in Example 1. Comparative treatment agent 2 was obtained.

[0107] Comparative Example 3

[0108] Compared with Example 1, the only difference is that in step 1, montmorillonite is used instead of kaolinite. All other operations and parameters are the same as in Example 1, and the corresponding comparative treatment agent 3 is prepared.

[0109] Comparative Example 4

[0110] Compared with Example 1, the only difference is that in step 1, maifanite is used instead of kaolinite, while other operations and parameters are the same as in Example 1, and the corresponding comparative treatment agent 4 is prepared.

[0111] Comparative Example 5

[0112] Compared with Example 1, the only difference is that step 2 was not performed, and modified kaolinite was directly used as the treatment agent to prepare the comparative treatment agent 5.

[0113] 1.2: Record the degradation effect

[0114] Test 1:

[0115] Simulated wastewater with perchlorate concentration of 800 mg / L, nitrate nitrogen concentration of 600 mg / L, and ammonia nitrogen concentration of 100 mg / L was used as the influent for this experiment. Sodium acetate was used as the carbon source, and the sludge concentration was 3500 mg / L. During the experiment, the pH value was 7.0~7.5, the dissolved oxygen was 0.2 mg / L, and the experimental temperature was 26℃. 300 mg / L of treatment agent (referring to the ratio of the mass of the added treatment agent to the total volume of sludge and wastewater in the reactor) was poured into the sequencing batch reactor (reaction volume of 5L). Samples were taken every 1 day to calculate the removal rates of perchlorate, ammonia nitrogen, and nitrate nitrogen. The permeate after 4 days of treatment was taken, and the concentrations of perchlorate, ammonia nitrogen, and nitrate nitrogen were measured (results are shown in Table 1).

[0116]

[0117] Test 2:

[0118] The treatment agent was prepared according to Example 1, using sodium acetate as the carbon source. During the experiment, the pH was 7.0–7.5, dissolved oxygen was 0.05–0.2 mg / L, and sludge concentration was 3000–5000 mg / L. The treatment agent was added to the reactor at a rate of 300 mg / L. Experiments were conducted on the heterotrophic microbial degradation of perchlorate under different perchlorate concentrations and temperatures. Water samples were taken every day to calculate the removal rates of perchlorate, ammonia nitrogen, and nitrate nitrogen. The permeate was collected after 4 days of treatment, and the concentrations of perchlorate, ammonia nitrogen, and nitrate nitrogen were measured. The results are shown in Table 2.

[0119]

[0120] Test 3:

[0121] The treatment agents prepared in each comparative example were used for test 1, and the results are shown in Table 3.

[0122]

[0123]

[0124] Note: The data in Table 4-a comes from the appendix. Figure 5 -a; Table 4-b data comes from Appendix Figure 5 -b; Table 4-c data comes from Appendix Figure 5 -c.

Claims

1. A composite treatment agent, characterized in that, Including modified kaolinite and enzymes; Modified kaolinite is a kaolinite material partially coated with iron oxide in situ, comprising kaolinite and iron oxide nanoparticles deposited in situ on part of the kaolinite surface; the preparation method of the modified kaolinite involves mixing kaolinite and a coupling agent, then adding water and a hydrophobic solvent for ultrasonic emulsification to obtain an O / W type emulsion. Subsequently, water-soluble ferric salt, water-soluble ferrous salt and alkaline components were added to the O / W type emulsion, and iron oxide nanoparticles were deposited in situ on the surface of kaolinite in contact with the aqueous phase in the O / W type emulsion to obtain the modified kaolinite. The enzymes mentioned include proteases and lipases.

2. The composite treatment agent as described in claim 1, characterized in that, In modified kaolinite, the area covered by iron oxide nanoparticles accounts for 30-60% of the kaolinite surface area.

3. The composite treatment agent as described in claim 1, characterized in that, Ferric oxide is deposited on one surface of kaolinite.

4. The composite treatment agent as described in claim 1, characterized in that, The weight ratio of ferric oxide to kaolinite is 0.2~0.4:

1.

5. The composite treatment agent as described in claim 1, characterized in that, The coupling agent is at least one of titanate coupling agents and silane coupling agents; The weight ratio of kaolinite to coupling agent is 1:0.005~0.025; The hydrophobic solvent is C4~C 10 Hydrocarbon solvents; The volume ratio of water to hydrophobic solvent is 1:0.5~5; The volume-to-weight ratio of water and hydrophobic solvent to kaolinite is 5~20 mL / g.

6. The composite treatment agent as described in claim 5, characterized in that, The weight ratio of kaolinite to coupling agent is 1:0.01~0.015; The volume ratio of water to hydrophobic solvent is 1:1 to 1.5; The volume-to-weight ratio of water and hydrophobic solvent to kaolinite is 10-15 mL / g.

7. The composite treatment agent as described in claim 1, characterized in that, Fe 2+ Fe 3+ The molar ratio is 2~4:

1.

8. The composite treatment agent as described in claim 1, characterized in that, The alkaline component is an alkali metal hydroxide.

9. The composite treatment agent as described in claim 1, characterized in that, The mass ratio of kaolinite to water-soluble ferrous salt is 2~5:

1.

10. The composite treatment agent as described in claim 1, characterized in that, The in-situ deposition temperature is 50~60℃.

11. The composite treatment agent as described in claim 1, characterized in that, The pH for in-situ deposition is 10-12.

12. The composite treatment agent as described in claim 1, characterized in that, The content of protease is 5000~20000U / g; the content of lipase is 3000~20000U / g.

13. A method for preparing the composite treatment agent according to any one of claims 1 to 12, characterized in that, It is obtained by mixing modified kaolinite and enzyme.

14. The application of the composite treatment agent according to any one of claims 1 to 12, characterized in that, It is used for the treatment of perchlorate wastewater.

15. The application of the composite treatment agent as described in claim 14, characterized in that, Perchlorate wastewater is wastewater that simultaneously contains ammonia nitrogen and / or nitrate nitrogen.

16. The application of the composite treatment agent as described in claim 15, characterized in that, In perchlorate wastewater, the concentration of perchlorate is 50~1200 mg / L, the concentration of nitrate is 50~800 mg / L, and the concentration of ammonia nitrogen is 20~200 mg / L.

17. The application of the composite treatment agent according to any one of claims 14 to 16, characterized in that, The dosage of the compound treatment agent in the treatment process is 100~500mg / L.

18. The application of the composite treatment agent as described in claim 17, characterized in that, During the degradation of perchlorate by heterotrophic microorganisms, the pH value was controlled between 7 and 7.5, the temperature between 2 and 35°C, and the dissolved oxygen between 0.05 and 0.2 mg / L.

19. The application of the composite treatment agent as described in claim 18, characterized in that, Activated sludge is also inoculated during the treatment process.

Citation Information

Patent Citations

  • Method for efficiently degrading perchlorate based on bioregenerable resin

    CN118324244A

  • Perchlorate wastewater treatment method

    CN119161063A

  • Treatment process of perchlorate wastewater

    CN118833958A

  • Wastewater treatment agent and preparation method therefor

    WO2022110091A1